HARAPAN ORANG TUA MENYEKOLAHKAN ANAKNYA DI LEMBAGA PENDIDIKAN ANAK USIA DINI TERPADU PONTIANAK BARAT - Asri Monika; M. Syukri; Dian Miranda (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThe aims of this research was to describe the expectations of parents sending their children to the Terpadu Early Childhood Education inWest Pontianak. The method used is a descriptive method with a qualitative approach. As for the data source is the parents of students. Data collection techniques using direct observation with observation guides, direct interviews with interview guides, and documentation with documentaries. From the results of the research that has been carried out it can be concluded that: Factors that encourage parents to send their children to the Terpadu Early Childhood Education in West Pontianak institution are factors that originate from within the parents such as parents' wishes so that their children can read, write and count. external factors such as social and economic status. The teacher has used various methods and media in learning so that children are happy and not bored in learning such as playing, singing, telling stories, demonstrations, conversing and giving assignments. But parents are more amenable to the method of assigning only the stationery media. The teacher can be a parent for the child and the teacher can also be a facilitator. Teachers can build good cooperation with parents, it's just better to be deeper in terms of handling children.Keyword     : Learning, Parent Expectations, Teacher Methods